2022-RA-1306-ESGO Effect of the COVID-19 pandemic on primary therapy and oncologic outcomes in women with advanced stage tubo-ovarian carcinoma in a tertiary cancer center. (20th October 2022) - Eriksson, Ane Gerda Z; Idland, Ragni K; Hoffmann, Larissa Elisabeth; Paulsen, Torbjørn; Wang, Yun; Jensen, Tone Skeie; Eyjolfsdottir, Brynhildur Eyjolfsdottir; Solheim, Olesya; Trent, Pernille Bjerre; Davidson, Ben; Dørum, Anne; Småstuen, Milada Cvancarova
Abstract : Introduction/Background: The COVID-19 pandemic resulted in significant alterations in access to health care services globally. The Norwegian Radium Hospital was declared 'Covid-free' to maintain cancer care at the same level as prior to the pandemic. Despite this, concerns regarding possible delayed diagnosis and suboptimal therapy have been raised.Objective: To explore if management and outcomes for women with advanced stage high-grade serous tubo-ovarian carcinoma (HGSC) was altered during the COVID-19 pandemic. Methodology: Women with stage III/IV HGSC from 2017–2021 were identified in our institutional database. Pre-Covid cohort January 2017 – March 2020, and Covid-cohort April 2020 – August 2021. Demographics, treatment characteristics and oncologic outcomes were compared between cohorts. Results: There were 354 (76%) and 114 (24%) women in the pre-Covid and Covid cohorts, respectively. Demographics did not differ between cohorts ( table 1 ). At multidisciplinary team evaluations there were no differences in allocation to primary surgery (PDS), interval surgery (IDS) or chemotherapy only (CT) between cohorts. Surgical complexity scores at PDS and IDS were similar in both cohorts. At PDS significantly more women in the covid cohort had residual disease <10 mm. Type and amount of chemotherapy did not differ between cohorts. Significantly more women in the Covid cohort received PARPi maintenance therapy. A significantly higher cumulative incidence of recurrence was found for the covid cohort (p<0.0003), figure 1a . For women undergoing exploratory laparotomy or IDS the risk of recurrence was higher in the Covid cohort than the pre-Covid cohort during initial 18 months after diagnosis, for IDS HR=2.75 [95% CI, 1.45–5.2], figure 1b . Conclusion: Despite equal surgical capacity and favorable prognostic characteristics, women with advanced stage HGSC diagnosed during the Covid pandemic had a significantly higher risk of recurrence when compared to pre-covid cohort, particularly for women undergoing IDS.